Development of a science process skills-based interactive website ‘bioenial’ on environmental pollution material - Rahmawati, Atika Budi; Bowo, Sugiharto; Santosa, Slamet (Universitas Negeri Jakarta, 2022)
This study aims to develop an interactive website based on the science process skill ‘Bioenial’ on Environmental Pollution material for grade X SMA/MA and identify the achievement of science process skills in the use of the 'Bioenial' website. This study was designed based on the Research & Development design from the Thiagarajan 4D development model (Define, Design, Develop and Disseminate). The instruments used in this study were media and material expert validation sheets, student worksheets, and student and teacher response sheets. The analysis technique used the Rasch analysis. The results showed that (1) the Feasibility of the 'Bioenial' website, the average percentage score of validity obtained from the three media experts was 97,4% that within the